2022
DOI: 10.1021/jacs.2c08364
|View full text |Cite
|
Sign up to set email alerts
|

Structural Descriptors to Correlate Pb Ion Displacement and Broadband Emission in 2D Halide Perovskites

Abstract: 2D hybrid lead halide perovskites exhibit versatile photoluminescent behaviors for narrowband to broadband emissions (BBEs) and have become attractive candidates for potential applications such as solid-state lighting. Establishing the relationship between the perovskite structural distortion and BBE is key but challenging in designing and optimizing the perovskite luminophores. Conventional attention is given to analyzing the intra-octahedron distortion of the [PbX6]4– (X = halide) unit that has not yet provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
65
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 73 publications
6
65
0
Order By: Relevance
“…In addition, we quantitatively analyzed the evolutions of the bandwidth of the PL peaks as shown in Figure S1b. We found that the bandwidth of the PL in Phase I is less than 14 nm, which is consistent with the free-exciton model established for narrow bands of PL emission for a wide range of 2D perovskites . Upon compression into Phase II, the bandwidth for both PL peaks increases almost linearly with pressure to several tens of nanometers, together with PL intensity reduction.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…In addition, we quantitatively analyzed the evolutions of the bandwidth of the PL peaks as shown in Figure S1b. We found that the bandwidth of the PL in Phase I is less than 14 nm, which is consistent with the free-exciton model established for narrow bands of PL emission for a wide range of 2D perovskites . Upon compression into Phase II, the bandwidth for both PL peaks increases almost linearly with pressure to several tens of nanometers, together with PL intensity reduction.…”
supporting
confidence: 87%
“…47 Additionally, the asymmetric emission profile has been associated with the structural distortion of PbI 6 octahedra, which is believed to be an important structural factor for emission band shape. 9,48 Upon compression, the intensity of the major PL peak increases until 0.8 GPa, where the peak intensity is about 10 times stronger than that at ambient pressure (Figure 3b), which indicates a remarkable pressure-enhanced PL efficiency. Concurrently, the PL emission peak becomes significantly more symmetric upon compression, which suggests a structural change to more regular (nondistorted) lead iodide octahedra.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Phonon changes will lead a lattice deformation and the position change of atoms in the cell. 34 As fluorescence occurs, electrons go back to the conduction band and minor deformations of the lattice are also corrected. When electrons are excited to the conduction band, small and irregular lattice deformations change the position of atoms, which affects the electron cloud density distribution and broadens the energy range of an electronic transition.…”
Section: Resultsmentioning
confidence: 99%